2016
DOI: 10.1002/art.39771
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IgA Plasmablast Levels in Subjects at Risk of Developing Rheumatoid Arthritis

Abstract: Objective The disease process in rheumatoid arthritis (RA) starts years before clinical diagnosis, and elevated disease-specific autoantibodies can be detected in this period. Early responses to known or novel autoantigens likely drive the eventual production of pathogenic autoimmunity. Importantly, the presence of disease-specific autoantibodies can identify individuals who are at high-risk for future RA onset but are currently without arthritis. The goal of the current studies is to characterize plasmablasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 58 publications
(100 reference statements)
3
71
0
2
Order By: Relevance
“…More recent studies have shown signs of local inflammation in bronchial tissues of untreated RA patients (Reynisdottir et al 2016). Using B cell barcoding techniques, the frequency of circulating IgA plasmablasts was found to be elevated in at risk subjects without RA who are ACPA positive providing further evidence for a mucosal origin for at least a proportion of the autoimmunity detected in RA (Kinslow J et al 2016). …”
Section: Interactions Between Genes and Environment: Ra As A ‘Mucosalmentioning
confidence: 91%
“…More recent studies have shown signs of local inflammation in bronchial tissues of untreated RA patients (Reynisdottir et al 2016). Using B cell barcoding techniques, the frequency of circulating IgA plasmablasts was found to be elevated in at risk subjects without RA who are ACPA positive providing further evidence for a mucosal origin for at least a proportion of the autoimmunity detected in RA (Kinslow J et al 2016). …”
Section: Interactions Between Genes and Environment: Ra As A ‘Mucosalmentioning
confidence: 91%
“…There is also a growing knowledge of how microbes influence human immunity both at mucosal surfaces and systemically. With relevance to RA pathogenesis, there is an emerging understanding of mucosal-associated immunoglobulin A (IgA)-related autoimmunity as a possible early factor in disease development that is based on autoantibody isotype studies as well as plasmablast studies (133, 134). …”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…antibodies to carbamylated proteins and heat-shock proteins (157159)), these aspects need to be included in models of disease development. Other processes that need to be explored include the role of neutrophil extracelluar traps (NETs) and inflammasomes in mucosal and systemic autoimmunity (160, 161), and emerging technologies that can elucidate single cell phenotypes (including IgA production) mucosally or systemically (134). Finally, it will be critically important to integrate all of these factors to understand how mucosal processes relate to other factors associated with RA such as genetics, familial factors, and sex, as well as environmental factors such as exposure to tobacco smoke, or dietary factors.…”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…Building a reference map of the human immune system is a difficult and complicated task; however, the dendritic cell atlas or the work of Wong et al characterizing T cells across tissues provide examples of the power of this approach [57••, 104•]. Incorporating data on from multiple assays to define lymphocyte profiles will be essential for understanding their functional impact, as shown by multiple studies that utilize repertoire sequences or expression data in combination with single cell cytometry to identify disease-relevant populations [71••,105•,106,107]. The development of new peptide-MHC multimeric complexes supports the detection and isolation of antigen-specific lymphocytes at much lower frequencies [108] than was previously feasible.…”
Section: The Future Of Single Cell Immunoprofilingmentioning
confidence: 99%